Sleeper agent : the atomic spy in America who got away - Hagedorn, Ann (Simon & Schuster, 2021)
"The little-known story of a spy on the atom-bomb project in World War II who had top security clearance -- American born, Soviet trained, he was never even suspected until after his information was in Soviet hands and he was safe in the USSR. It's LeCarre and "The Americans" for real"--